A associação entre infecção crônica por Toxoplasma gondii e transtorno depressivo no terceiro trimestre de gestação determina mudanças no balanço de citocinas pró-inflamatórias e anti-inflamatórias - Carvalho, Ricardo José Victal de (2019)
Depressive disorder in pregnancy is frequent (10-15% in some statistics) and associated with some adverse pregnancy outcomes, like inadequate prenatal care, drug abuse, fetal growth restriction, and others. In the way to better understand the biology of mental disorders, besides the neurotransmitter’s theories, the next step is to find biological agents (pathogens) as well as immunologic markers associated to psychopathologic symptoms. Toxoplasma gondii has been associated with some mental disorders in general population, and depressive disorder and anxiety in pregnancy. Depressive disorder in pregnancy is associated to some immunologic marker changes, like cytokines. We aim to investigate the relation of depressive disorder, positive serology to chronic toxoplasmosis and the cytokine immunologic response (TNF-α, IFN-γ, TGF-β1, IL-6, IL-8, IL-10 and MIF) in 79 pregnant women (age 18-40 years) in the third trimester of uncomplicated pregnancy. They answered the EPDS SCALE (Eddinburg Postnatal Depression Scale) during their routine prenatal consults, and blood sample was collected during their routine prenatal periodic exams. Elisa was used to the cytokine levels measurement. The results show that, comparing to pregnant women without depression, pregnant women in the third trimester of gestation, with depressive disorder, shows diferente cytokine response (higher titles of IL-10, TNF-α, TGF-β1 and smaller titles of IL-8). Compared to pregnant women without positive serology to chronic T. gondii, pregnant women with positive serology shows higher titles of IL-10 and IL-6 and smaller titles of IL-8. In the association of the two clinical situations we found higher titles of IL-10, IL-6 and TNF-α; and smaller titles of IL-8 and specifically MIF. Than, we concluded that, in the association of the tree events, pregnant women in the third trimester of pregnancy, with chronic toxoplasmosis and with depressive disorder diagnosis, the pattern of immunomodulatory immune responses shows expressive changes in the citokynes levels. However, these alterations wouldn’t be sufficient to exacerbate the depression during the pregnancy